2021
DOI: 10.3390/jcm10215182
|View full text |Cite
|
Sign up to set email alerts
|

Hemoadsorption in ‘Liver Indication’—Analysis of 109 Patients’ Data from the CytoSorb International Registry

Abstract: Background: Our aim is to report the results of the ‘liver indication’ subset of patients in the CytoSorb International Registry. Methods: Structured data were recorded. Treatment characteristics and changes from T1 (start of hemoadsorption) to T2 (termination) were evaluated with a special focus on bilirubin, C-reactive protein, procalcitonin, interleukin-6, platelet levels, SOFA scores, mortality, and subjective assessment by the attending physicians. Results: Until January 2021, from the total 1434 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
32
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 31 publications
4
32
1
Order By: Relevance
“…3 However, a recent in-vitro study demonstrated a superior bilirubin removal and comparable bile acids removal efficacy by Cytosorb ® compared to MARS. 8 The largest cohort of Cytosorb ® use for hyperbilirbinemia comprising 109 critically ill adults reported a mean drop of bilirubin level of 78.2 μmol/L after a median treatment of two sessions lasting for 43 h. 5 Our own experience also showed that hemoadsorption may have the merits of a faster initial rate of bilirubin removal and ease of set up compared to albumin dialysis.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…3 However, a recent in-vitro study demonstrated a superior bilirubin removal and comparable bile acids removal efficacy by Cytosorb ® compared to MARS. 8 The largest cohort of Cytosorb ® use for hyperbilirbinemia comprising 109 critically ill adults reported a mean drop of bilirubin level of 78.2 μmol/L after a median treatment of two sessions lasting for 43 h. 5 Our own experience also showed that hemoadsorption may have the merits of a faster initial rate of bilirubin removal and ease of set up compared to albumin dialysis.…”
Section: Discussionmentioning
confidence: 93%
“…1 It has been demonstrated that the use of extracorporeal liver support (ECLS) system is associated with a reduced mortality. 2 There are a number of different ECLS modalities including single-pass albumin dialysis (SPAD), 3 molecular adsorbent reticulating system (MARS), 3 fractionated plasma separation and adsorption (Prometheus ® ), 3 therapeutic plasma exchange (TPE), 4 and hemoadsorption, 5 but no single modality is superior to the others as large-scale trials directly comparing their efficacy is lacking. In recent years, hemoadsorption has re-attracted attention with the introduction of a new sorbent Cytosorb ® , which is made of biocompatible porous polymer beads that is capable of removing hydrophobic molecules up to the size of 55–60 kDa.…”
Section: Discussionmentioning
confidence: 99%
“…Both in children and in adults, CytoSorb ® has been used to significantly and effectively reduce bilirubin and myoglobin serum concentrations, proving itself as a potential tool for patients with different forms of liver failure with hyperbilirubinemia [55,56] and rhabdomyolysis [57,58].…”
Section: Cytosorb ® Hemoperfusionmentioning
confidence: 99%
“…9,10 Severals of publications reported on its innate ability to reduce inflammatory parameters (C-reactive protein [CRP], procalcitonin [PCT], Interleukin [IL]-6, tumor necrosis factor [TNF]-α). 11…”
Section: Introductionmentioning
confidence: 99%
“…9,10 Severals of publications reported on its innate ability to reduce inflammatory parameters (C-reactive protein [CRP], procalcitonin [PCT], Interleukin [IL]-6, tumor necrosis factor [TNF]-α). 11 This observational pilot paper describes a case series of DCD donors measuring inflammatory cytokine levels under hemoadsorption treatment during NRP.…”
Section: Introductionmentioning
confidence: 99%